(3GdHOQ GdefjQ aj Yde GdJYHjQs - (3CMeO Hf YHO GdQMef Hf YHO GdefYe Hf SdWGf Hf eSQhQ GdebOSj, TgGH GdOjf CHj GdYHGSs ((3CMeO GdHSJi s)
(3ChdgG (B:s
(3GdMeO ddg Mb MeOg hHYO aEfg fOHfi LeGYI Edi LeY ebOeI ai Yde GdefGe s
(3BNQgG (B:s
(3hGdMeO ddg Ydi fYeJg GdJi dG JMUi s
(3GdfSNI HgG MhGTs
(3fSNI NRGFfjI hHChdgG dhMI efbhTI hePgHI HQSe GdebQ GdCTQai GdYGdi Gdehdi GdbVGFis
(3bQf GdfSN (B:s
(3GdbQf GdKGefs
(3GdJhKjbGJ GdeQLYjI (B:s
(3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA (B4 - (3bSe eYGQa YGeI (B- (3U (B123 s
Keywords: (3JYHjQ GdQDjGs